(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2016)
An experiment was conducted on growth, survival and flesh quality of fingerlings of stinging catfish, Heteropneustes fossilis (Bloch, 1794) were evaluated using three types of feeds namely live tubificid worm, tubificid powder and commercial pellet feed. Three feeds were used in three treatments where Treatment-T1with pellet feed (control), Treatment-T2 with tubificid powder and Treatment-T3 having live tubificid worms. Twenty fingerlings (8.04 ± 0.01 g) were released in each 50 L tank for 45 days rearing. The fishes were fed twice a day at 10% of body weight for first 15 days and that of 8% per day for the next 30 days. Sampling was conducted fortnightly. Significant higher mean weight 48.53 ± 1.13 g was observed in stinging catfish at the 45th day fed with live tubificid worms than those of others (P<0.05). The highest survival rate was 83.33±4.41%, average daily gain 0.90 ± 0.03 g day-1, specific growth rate 3.99 ± 0.05%, food conversion ratio 1.65 ± 0.10 and protein content 17.48 ± 0.28% were found at the 45th day of treatment T3 when live tubificid worms were used as feed. Live tubificid worms can be used as a good alternative to commercial feed in rearing of stinging catfish. Bangladesh J. Sci. Ind. Res. 51(3), 175-182, 2016